Long-Term Survival and PSA Control with Radiation and Immunotherapy for Node Positive Prostate Cancer - M. Kamrava (Clinical and Developmental Immunology, 2009)
We describe a patient with node positive prostate cancer treated with radiation, androgen deprivation, and immunotherapy with long-term overall survival and PSA control. ELISPOT immunoassay studies demonstrated PSA specific T-cells prior to starting vaccine therapy suggesting that this positive response may be related to an improved antitumor immune response of the patient, increased immunogenicity of the tumor, or decreased activation of immune escape pathways. Further evaluation of therapeutic cancer vaccines in combination with radiation and hormonal therapy in the definitive management of prostate cancer is warranted.